INTERNALISASI PERSONAL HYGIENE DALAM PRODUKSI MAKANAN HALALAN THOYYIBAH - Nikmatul Masruroh Nikma; Rasya Madaniah Nurul Islami; Frenda Ninggar Marsiska (Studi Kasus Inovasi Ekonomi, 2025)
Food production must go through a healthy and clean process. Especially in this era, we must follow the concept of halalan thoyyibah so that food products can be easily accepted by consumers. Therefore, PT. Mitratani Dua Tujuh Jember applies rules on personal hygiene, not only employees but to everyone who enters the production room of food products produced, for example to the production site of edamame and other products. The problem that arises is personal hygiene which is understood as a rule, not as a principle of life that must be carried out voluntarily in production activities. So, there is still punishment for employees who do not comply. This personal hygiene should be carried out as a life principle in carrying out production. So that it becomes a healthy and halal lifestyle. Therefore, this service uses collaborative and educational service techniques in order to provide assistance to internalize the principles of personal hygiene to the employees of PT Mitratani Dua Tujuh about the importance of implementing personal hygiene in the food production process not because of the rules alone, but must be a guide for life in carrying out production activities. Moreover, export-based food. This service resulted in the understanding and discipline of production actors who are part of the production process at PT. Mitratani Dua Tujuh. Personal hygiene determines halal production. This is because food products from PT. Mitratani Dua Tujuh not only produce HACCP and BRC certified products but also halal certified. Thus, the products produced apply the principles in the production of halal food thoyyibah.